2014
DOI: 10.1002/ppul.22986
|View full text |Cite
|
Sign up to set email alerts
|

Perceived neighborhood safety and asthma morbidity in the School Inner‐City Asthma Study

Abstract: Summary Aim: The aim of this study was to investigate whether neighborhood safety as perceived by primary caregivers is associated with asthma morbidity outcomes among inner-city school children with asthma. Methods: School children with asthma were recruited from 25 inner-city schools between 2009 and 2012 for the School Inner-City Asthma Study (N = 219). Primary caregivers completed a baseline questionnaire detailing their perception of neighborhood safety and their children’s asthma symptoms, and the childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 37 publications
(81 reference statements)
3
24
0
Order By: Relevance
“…Caregiver report of violence and perception of unsafe neighbourhoods have been associated with increased asthma symptoms in inner-city children. 17, 18 Across cultures, children who report being victimized or feeling unsafe have higher odds of having an asthma episode, medication and healthcare use. 19, 20 The healthcare use tends to be weighted towards emergency services, despite reportedly good access to the primary physician’s office.…”
Section: Psychosocial Stress Exposure To Violence and Asthma Controlmentioning
confidence: 99%
“…Caregiver report of violence and perception of unsafe neighbourhoods have been associated with increased asthma symptoms in inner-city children. 17, 18 Across cultures, children who report being victimized or feeling unsafe have higher odds of having an asthma episode, medication and healthcare use. 19, 20 The healthcare use tends to be weighted towards emergency services, despite reportedly good access to the primary physician’s office.…”
Section: Psychosocial Stress Exposure To Violence and Asthma Controlmentioning
confidence: 99%
“…Among adults, feeling unsafe is associated with adopting poorer health habits (e.g., increases in sedentary behavior, decreased physical activity, and active transportation), and experiencing poorer mental (e.g., anxiety, deteriorated psychological wellbeing, and social withdrawal) and physical (e.g., poorer self-reported health, stressrelated diseases, and chronic conditions) health. [7][8][9][10] With respect to child health, parent perceived unsafety is associated with asthma, 11 sleep problems, 12 psychological distress, 13 and weight-related behaviors (e.g., physical activity). 14 Parents' perceptions of safety may influence child health by impacting the household environment and parenting decisions (e.g., restricting children's outdoor activities).…”
mentioning
confidence: 99%
“…32 Smith et al reported that suboptimal asthma control and controller medication underuse were highly associated with potentially modifiable risk factors, especially low parental expectations for functioning and symptom control, discordant estimation of asthma control, lack of routines for administering medication, and concerns about asthma medications. 39 Psychosocial factors, particularly the mental health of children and caregivers, are significant factors in predicting asthma morbidity. Increased exposure to violence predicts increased symptomatology in a graded fashion.…”
Section: Adherencementioning
confidence: 99%